Breast cancer : current and emerging trends in detection and treatment - Smith, Terry L. (Terry Lane), 1944- (2006)
Examines the history of breast cancer, explains what it is, who gets it, available treatments, preventive measures, and research being done on the disease.
Breast cancer throughout history -- What is breast cancer? -- Who gets breast cancer? -- Treatment for breast cancer -- Can we prevent breast cancer? -- The promise of research.
Includes bibliographical references (pages 58-61) and index.
Keywords: Breast -- Cancer; Cancer; Diseases